Exploitation of children in the 21st century – socially neglected childhoods - Stanič, Tanja (Teorija in praksa, 2023)
Childhood is socially constructed, depending on social, economic and cultural circumstances. Poverty, social differences, conflicts, and social injustice have a negative impact on children’s lives. The aim of the article is to present childhoods under conditions of exploitation. Despite general progress, and the emancipation of children’s rights, data confirm an increase in the number of children who are engaged in war conflicts, perform difficult and inappropriate work, or in slavery. In conclusion, the exploitation of children is considered in the context of social conditions and processes, neoliberal capitalism, globalisation, and documents that guarantee children’s rights.
Keywords: childhood; childrens's rights; družbene neenakosti; exploitation; globalisation; globalizacija; izkoriščanje; Izkoriščanje (etika); Otroci; otrokove pravice; otroštvo; social inequalities